Teknik Evaluasi Pembelajaran PAI - Imam Nur Rohmat; Muhammad Nur Karim Setyawan; Izatul Aini Salsabila (Prodi Pendidikan Agama Islam IAI Al-Qodiri Jember, 2023)
This study aims to analyze the techniques and steps used in evaluating PAI learning. Qualitative approach and literature study method. First, data collection techniques were used by reviewing various literature sources derived from various documents, both from books, journals, discussions with experts relevant to the study. Second, after that if the data is collected, data analysis is carried out. Furthermore, the author uses content analysis techniques, namely by interpreting data, adding explanations, and drawing conclusions. This study shows that; 1) the evaluation of PAI learning aims to measure the development of students during the learning process so that its effectiveness and efficiency can be known. If there is a discrepancy between the learning process and the planning, PAI educators are responsible for improving and overcoming the problems found. 2) Some learning evaluation techniques are planning and development evaluation, monitoring evaluation, impact evaluation, economic-efficiency evaluation, comprehensive program evaluation. 3) The steps of PAI learning evaluation include determining evaluation objectives, data analysis, interpretation of results, providing feedback, developing improvements, reporting and reflection. The results of this study provide important benefits, including encouraging the development of better evaluation strategies to help teachers and students achieve a deeper understanding of Islamic values, improving the quality of PAI teaching, curriculum development, measuring student progress.